A Microbiology Module Development on Antagonism Between Fungi and Bacteria Based on Problem-Based Learning to Improve Student’s Critical Thinking Skills - Maknuna, Durrotul; Hastuti, Utami Sri; Prabaningtyas, Sitoresmi (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
The purpose of the research is to develop Microbiology Module on the topic